Kerelatifan aksiom-aksiom utiliti tunggal nash dengan aksiom-aksiom von neumann-morgenstern - Lilysuriazna Raya; Mohammad Alinor Abdul Kadir (Penerbit ukm, 2006)
From the time when Nash proposed 8 axioms as the basic to understand the individual utility theory, many scholars such as Schmidt, Sobel, Gerber and van Damme anticipated that in understanding the same theory, the axioms were strongly influenced by the 5 axioms previously proposed by von Neumann and Morgenstern. There was no established mathematical proof to support these views, which so far were only supported by personal observations and at the most, mathematical substantiation to correlate some of the Nash and von Neumann-Morgenstern axioms. In this study, we compellingly proved that the 6 axioms of Nash were strongly influenced by 5 von Neumann and Morgenstern axioms. We forward our views on the position of the remaining 2 Nash’s axioms